PHRASE THEORY: PHRASE TYPES AND SUBTYPES: COORDINATE, SUBORDINATE AND PREDICATIVE PHRASES (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides a detailed overview of the various organs involved in speech production, emphasizing the coordination and roles of each component in the process. It begins by describing the respiratory system as the power source, explaining how air from the lungs is used to generate sound. The role of the larynx in sound production through vocal cord vibration is explored, followed by an examination of how the articulators—such as the tongue, lips, and palate—shape these sounds into recognizable speech